Citric acid production by different local isolates of mushrooms Aspergillus niger - Mohammed Qasem; enam Al-Hamadani (College of Education for Pure Sciences, 2007)
Thirty two different local isolates of the fungus Aspergillus niger were obtained from different sources such as (seeds , plant parts , soil , air , and plants callus infected with the fungus).The local isolates were compared with their efficiencies to produce citric acid. Production of citric acid by the isolate obtained from chickpea seeds highly exceeded that produced by other isolates of the fungus .The production of citric acid by this isolate was( 20.41g 1 )after ten days of incubation.